Becoming solution-focused in brief therapy - Walter, John L.; Peller, Jane E. (New York : Brunner/Mazel, 1992)
A practical guide to becoming solution-focused and construction solutions in brief therapy.
Includes bibliographical references (p. 260-262) and indexes.
Keywords: Solution-focused brief therapy; Problem Solving; Brief psychotherapy